2015
DOI: 10.1088/0004-637x/807/2/144
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structure and Dynamics of the Erupting Solar Polar Crown Prominence on 2012 March 12

Abstract: We present an investigation of the polar crown prominence that erupted on 2012 March 12. This prominence is observed at the southeast limb by the Solar Dynamics Observatory (SDO)/Atmospheric Imaging Assembly (AIA; end-on view) and displays a quasi-vertical thread structure. A bright U-shaped or horn-like structure is observed surrounding the upper portion of the prominence at 171 Å before the eruption and becomes more prominent during the eruption. The disk view of STEREOB _ shows that this long prominence is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 64 publications
6
69
0
1
Order By: Relevance
“…Our resulting magnetic field also shows a certain separation between the flux rope axis and top most dips as suggested by cavity observations (Hudson et al 1999;Régnier et al 2011;Gibson 2015;Filippov et al 2015;Su et al 2015;Bak-Steslicka et al 2016). This is due to the curved geometry of the flux rope.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Our resulting magnetic field also shows a certain separation between the flux rope axis and top most dips as suggested by cavity observations (Hudson et al 1999;Régnier et al 2011;Gibson 2015;Filippov et al 2015;Su et al 2015;Bak-Steslicka et al 2016). This is due to the curved geometry of the flux rope.…”
Section: Resultssupporting
confidence: 78%
“…In this framework, Zuccarello et al (2014) studied the evolution of an active region filament and concluded that at the time of the eruption the filament had an height where the decay index is  n 1. Su et al (2015) studied the eruption of a polar crown prominence and found that at the moment of the eruption the critical decay index was =  n 1 0.2, depending on whether the top of the prominence or the center of the cavity was used to locate the height of the erupting structure.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, n measures the run of the strapping field's confinement with height. Theoretical works predict the onset of torus instability when n is in the range of 1.5, 2.0 & Török 2006), while observations of eruptive prominences suggest a critical value n 1 (Filippov 2013; Su et al 2015).It is suggested that the former value is representative for the top of the flux rope axis, while the latter value is typical for the location of magnetic dips that hold the prominence material (Zuccarello et al 2016). Therefore, n 1, 1.5 = [] are used as critical decay index values for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The decay index was computed in regions above the photosphere from a potential field extrapolation (Liu 2008;Guo et al 2010;Kumar et al 2012;Nindos et al 2012;Xu et al 2012;Zuccarello et al 2014;McCauley et al 2015;Su et al 2015) or a nonlinear force-free field (NLFFF) extrapolation Cheng et al 2011;Savcheva et al 2012) to find the difference in coronal magnetic fields for failed eruptions and full eruptions, a threshold of flux rope instability, the relationship between the decay index and the CME speed, and so on.…”
Section: Introductionmentioning
confidence: 99%